Dr Werner Treitz leaves CTA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Dr Werner Treitz, formerly Technical Adviser, Deputy to the Director, has now retired from CTA. Born on 22nd April 1927 at Korschenbroich in the Federal Republic of Germany, Dr Treitz obtained his doctorate in agricultural science in 1952 at...